Chemical pre-treatment on palm oil clinker as partial cement replacement material in mortar - Nor Syahirah, Mahmudin (2019)
The production of cement is increasing day by day due to the rapid urban expansion. Highly demands in cement production emits more carbon dioxide to the environment thus leads to the unsustainable environment. At that time, improper disposal of solid waste materials results on the pollution to occur consecutively. Palm Oil Clinker (POC) is a by-product of palm oil mill which can be found in large quantity in Malaysia and it is considered as waste. Hence, by channelling the solid waste into the construction industry as cement replacement materials helps to overcome those problems. The aim of this research is to study the effects of treated and untreated palm oil clinker ash into the mortar mixture based on the compressive strength and porosity comparing to that conventional mortar mixture. Basically, chemical pre-treatment process is conducted to stimulate the pozzolanic reaction of amorphous silica with calcium hydroxide in the mortar. The pre-treatment of palm oil clinker ash is conducted by using hydrochloric acid (HCl) which purposely to remove heavy metals that present in the ash beside helps in extracting a high amount of silica from the ash. The ash was then impregnated in the dilution of 0.1 M hydrochloric acid for 1 hour before it was dried in oven forming treated ash for the cement replacement material. POCP were studied at various replacement levels of treated and untreated POCP at 5%, 10% and 15% of the original total weight of the Ordinary Portland cement respectively. The mortar was mixed and cast in 50 mm x 50 mm x 50 mm mould and left 24 hours for the hardening process. The specimens are demoulded and left cured for 3, 7, 28 and 56 days consecutively before it was taken out for the compressive strength and porosity testing. The results indicate that at the early stages, the pozzolanic reaction for T5, T10 and T15 is faster than the control specimen thus resulting in higher compressive strength. The reaction starts to slow down at day 28 up to day 56 causing the maximum compressive strength attained the highest by the control samples. More amorphous silica forming the additional calcium-silicate-hydrate (C-S-H) bond at the early days making the mortar stronger and denser. However, T5 and T10 able to gain 98% of the control specimen strength respectively. It should be noted that the use of POCP reduced the compressive strength at a remarkable rate. The statistical data proved that there was no significant difference in compressive strength of the control specimen and T5 in the mortar. While the results on porosity show that increase in the amount of POCP into the mortar mixture had reduced the water usage into the mortar due to the pozzolanic reaction that took place through the formation of C-S-H gel. Replacement of high percentage of POCP unable to form a stronger mortar due to a porous structure that results in poor interlocking bond and poor blending properties between ash particles and cement particles. Last but not least, this research reveals that the POC can be used as cement replacement materials as it is a highly beneficial material contributing substantially toward the sustainable environment and development. To conclude, by using 0.1 M of hydrochloric acid at 1-hour duration for pre-treatment process, the most optimum proportion is attained by T5 because of its ability to produce 98% of control samples’ compressive strength and also with the presence of fewer voids in the mortar.